Determining Multi-Criteria Supplier Selection towards Sustainable Development of IT Project Outsourcing - Fauziah Baharom; Prashaya Fusiripong; Yuhanis Yusof (International Journal of Supply Chain Management, 2017)
Due to competitiveness in the global business, many organizations have sought alternative to improve their businesses and operations by outsourcing projects and this includes Information Technology (IT) projects. Selecting the most suitable IT supplier is important to ensure sustainable development of the projects. Supplier is selected based on a set of criteria used in the decision process. The criteria can be comprised into tangible and intangible criteria. Many studies have attempted to determine the criteria to be used in selecting IT supplier, nevertheless, it has yet to be reported on a standardize set of criteria to be used in IT outsourcing projects. Thus outsourcing decisions are often made under uncertainty and incomplete information which leads to weak decision and high risk of projects failure. Therefore, the study aimed to determine multi-criteria for supplier selection in order to ensure the sustainable development of IT outsourcing projects. The criteria were identified using comprehensive review approach that utilizes searching information related to multi criteria supplier selection in IT outsourcing and successful criteria of IT outsourcing projects. As a result, the identified criteria is proposed as a standardize criteria in selecting supplier for IT outsourcing projects. Such a contribution is hoped to benefit businesses for various IT outsourcing projects.